David van der Linden, „Experiencing Exile: Huguenot Refugees in the Dutch Republic”, 1680-1700 [Politics and Culture in Europe, 1650-1750], Ashgate 2015, 291 p., ISBN 978-1-4724-2927-8 - OANCEA, Sever (Studia Universitatis Babeș-Bolyai Historia, 2015)
This book by David van der Linden, a Dutch young scholar with solid expertise on French immigration in Early Modern Europe, deals with Huguenot exiles in the Dutch Republic. Albeit the topic is not new within the European or even American scholarly debates, the approach it employs stands out, indeed. The author aims to analyze the experience of ordinary refugees and not only that of the elites, “rather than covering the process of integration or fortunes of elite Huguenots, it re-inserts the vast masses of refuges into the history of exile“(p.8). In my view, this may represent an intended collective biography of a Protestant group, which includes both a social and a cultural perspective that may be integrated into a broader history of the Huguenot Church. The investigated period is 1680-1700 which witnessed high levels of tension across the European continent, as well as an intensification of religious exile. The approach is both chronological and analytical, while the presentation is structured into three main parts, namely “The economy of exile”, “Faith in exile” and “Memories in Exile.”